Therapeutic drug monitoring of antiretroviral drugs in HIV-infected patients - Punyawudho B. (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Introduction: Therapeutic drug monitoring (TDM) may be beneficial when applied to antiretroviral (ARV). Even though TDM can be a valuable strategy in HIV management, its role remains controversial. Areas covered: This review provides a comprehensive update on important issues relating to TDM of ARV drugs in HIV-infected patients. Articles from PubMed with keywords relevant to each topic section were reviewed. Search strategies limited to articles published in English. Expert commentary: There is evidence supporting the use of TDM in HIV treatment. However, some limitations need to be considered. The evidence supporting the use of routine TDM for all patients is limited, as it is not clear that this strategy offers any advantages over TDM for selected indications. Selected groups of patients including patients with physiological changes, patients with drug-drug interactions or toxicity, and the elderly could potentially benefit from TDM, as optimized dosing is challenging in these populations.